a -> g(c)

g(a) -> b

f(g(

R

↳Removing Redundant Rules for Innermost Termination

Removing the following rules from

g(a) -> b

R

↳RRRI

→TRS2

↳Removing Redundant Rules

Removing the following rules from

a -> g(c)

where the Polynomial interpretation:

was used.

_{ }^{ }POL(c)= 0 _{ }^{ }_{ }^{ }POL(g(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(b)= 1 _{ }^{ }_{ }^{ }POL(a)= 1 _{ }^{ }_{ }^{ }POL(f(x)_{1}, x_{2})= x _{1}+ x_{2}_{ }^{ }

Not all Rules of

R

↳RRRI

→TRS2

↳RRRPolo

→TRS3

↳Removing Redundant Rules

Removing the following rules from

f(g(X), b) -> f(a,X)

where the Polynomial interpretation:

was used.

_{ }^{ }POL(g(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(b)= 0 _{ }^{ }_{ }^{ }POL(a)= 0 _{ }^{ }_{ }^{ }POL(f(x)_{1}, x_{2})= x _{1}+ x_{2}_{ }^{ }

All Rules of

R

↳RRRI

→TRS2

↳RRRPolo

→TRS3

↳RRRPolo

...

→TRS4

↳Dependency Pair Analysis

Duration:

0:00 minutes